Organizing collaboration: Ottawa's Role in Homelessness Initiatives - Sarah Carneiro (10863948) (2019)
On any given night in Canada, 35,000 individuals experience some form of homelessness and between 136,000 and 156,000 Canadians access emergency shelters each year. Homelessness is a daunting policy and administrative challenge that requires the concerted collaboration of a diversity of public and private sector players to tackle. I argue that the Canadian federal government’s leadership prompted the cooperation between the different orders of government and non-governmental organizations (NGOs) in St. John’s, Newfoundland and that its administrative and collaborative governance approach has generated impressive outcomes in responding to the complicated issue of homelessness. The community-based, shared funding model used by Ottawa has proven effective in harmonizing homelessness programming, data collection, indicators of success, and objectives and outcomes between governmental and nongovernmental partners.